O perfil do bibliotecário para mediar a Lei de Acesso à Informação: um estudo nas universidades públicas de Belém - SANTOS, Janilce Rodrigues dos (2017)
This research seeks to analyze the profile of the professional librarian as to the operationalization, mediation and effectiveness of access to information in the Public Universities of Belém do Pará. Law acquired through Federal Law 12.527 of November 18, 2011, on campus Of the following universities: Federal University of Pará; University of the State of Pará, Federal Rural University of Amazonia and the Federal Institute of Pará. Law 12,527/2011 provided greater citizen participation and care in the treatment of public information that presents rules for its access. Considering this scenario imposed by the law is that the Public Universities of Belém need to change and adapt to the rights acquired by the citizen when requesting the public information. Therefore, it is believed that the professional librarian presents facilitating elements that could mediate this process of requesting public information, further encouraging the importance of transparency in the Public Universities of Belém. In the course of making access to information important, it is important to understand the factors And how the librarian can intervene in this process and propose mechanisms that facilitate the needs of the citizen. In order to achieve this purpose, the methodology classified as exploratory and descriptive used the field research as a way of collecting data through an interview with the professionals who work in the Citizen Information Services of the Public Universities of Belém do Pará. This instrument makes it possible to know the operation of the SIC's of the researched universities. The data will be treated by means of descriptive statistics and presented in tables and tables. The results made it possible to reveal the profile of the SIC leaders and how the librarian can act by mediating and democratizing access to public information in search of the efficiency of this right acquired by the citizen. Finally, suggestions are proposed highlighting the profile of the librarian in the mediation of Law 12,527/2011 in the public universities of Belém do Pará.